[(CH3)2NH(CH2)2NH(CH3)2][(UO2)2F2(HPO4)2]: a new organically templated layered uranium phosphate fluoride--synthesis, structure, characterization, and ion-exchange reactions. - Min Ok, K; Doran, M; O'Hare, D (2007)
A new organically templated layered uranium phosphate fluoride, [(CH(3))(2)NH(CH(2))(2)NH(CH(3))(2)][(UO(2))(2)F(2)(HPO(4))(2)] has been synthesized by hydrothermal reaction of UO(3), H(3)PO(4), HF, and (CH(3))(2)NCH(2)CH(2)N(CH(3))(2) at 140 degrees C. [(CH(3))(2)NH(CH(2))(2)NH(CH(3))(2)][(UO(2))(2)F(2)(HPO(4))(2)] has a layered crystal structure consisting of seven-coordinated UO(5)F(2) pentagonal bipyramids and four-coordinated HPO(4) tetrahedra. Each anionic layer containing three-, four-, and six-membered rings is separated by [(CH(3))(2)NH(CH(2))(2)NH(CH(3))(2)](2+) cations. The [(CH(3))(2)NH(CH(2))(2)NH(CH(3))(2)](2+) cations may be readily exchanged with the M(2+) ions (M = Ba, Sr and Ca) in water to give high crystalline AE(UO(2))(2)(PO(4))(2).6H(2)O (AE = Ca, Sr, Ba).